Superior Energy‐Storage Capacitors with Simultaneously Giant Energy Density and Efficiency Using Nanodomain Engineered BiFeO3‐BaTiO3‐NaNbO3 Lead‐Free Bulk Ferroelectrics - Qi, He; Xie, Aiwen; Tian, Ao; Zuo, Ruzhong (Advanced energy materials, 2020)
Dielectric capacitors are receiving a great deal of attention for advanced pulsed power owing to their high power density and quick charge/discharge rate. However, the energy density is limited and the efficiency and the thermal stability are also not ideal, which has been a longstanding obstacle to developing desirable dielectric materials. These concerns have are addressed herein by fabricating nanodomain‐engineered BiFeO3‐BaTiO3‐NaNbO3 bulk ferroelectrics, integrating a high‐spontaneous‐polarization gene, wide band gaps, and a heterogeneous nanodomain structure, generating record‐excellent comprehensive performance of giant energy‐storage density Wrec ≈8.12 J cm−3, high efficiency η ≈90% and excellent thermal stability (±10%, −50 to 250 °C) and ultrafast discharge rate (t0.9 < 100 ns). Significantly enhanced dielectric breakdown strength of BiFeO3‐based solid solutions is mainly attributed to the substitution of NaNbO3, which provides an increased band gap, refined grain size, and increased resistivity. The formation of nanoscale domains as evidenced by piezoresponse force microscopy and transmission electron microscopy enables nearly hysteresis‐free polarization‐field response and temperature‐insensitive dielectric response. In comparison with antiferroelectric capacitors, the current work provides a new solution to successfully design next‐generation pulsed power capacitors by fully utilizing relaxor ferroelectrics in energy‐storage efficiency and thermal stability. Superior energy‐storage performance of a giant energy‐storage density Wrec ≈8.12 J cm−3, a high efficiency η ≈90%, and an excellent thermal stability (±10%, −50 to 250 °C) and an ultrafast discharge rate (t0.9 < 100 ns) are reported in a nanodomain engineered BiFeO3‐BaTiO3‐NaNbO3 bulk ferroelectrics integrating a high spontaneous polarization gene, wide band gap, and a heterogeneous nanodomain structure, showing good potential for next‐generation pulsed power capacitors.